Cancer in pregnancy increases the risk of venous thromboembolism: a nationwide cohort study. (6th January 2021) - Greiber, IK; Mikkelsen, AP; Karlsen, MA; Storgaard, L; Viuff, JH; Mellemkjær, L; Hjortshøj, CS; Lidegaard, Ø
Abstract : Objective: To investigate if cancer in pregnancy causes a higher risk of venous thromboembolism (VTE) during pregnancy and postpartum compared with pregnant women without cancer. Design: A historical prospective cohort study using data from nationwide registries. Setting and population: We assessed all pregnancies in Denmark between 1 January 1977 and 31 December 2017. Methods: We linked information concerning cancer diagnosis, pregnancy and VTE diagnosis and potential confounders. Event rates of VTE for women with pre‐pregnancy cancer, cancer in pregnancy and without cancer were calculated per 10 000 pregnancies and compared using logistic regression analysis. Main outcome measures: Occurrence of VTE during pregnancy or the postpartum period. Results: A total of 3 581 214 pregnancies were included in the study and we found 1330 women with cancer in pregnancy. In pregnant women with cancer, the event rate of VTE was 75.2 per 10 000 pregnancies compared with 10.7 per 10 000 pregnancies in the no cancer group. The findings correspond to an increased adjusted odds ratio of 6.50 (95% CI3.5–12.1) in the cancer in pregnancy group in comparison with the no cancer group. Conclusions: Women with cancer in pregnancy have a markedly higher risk of pregnancy‐associated VTE compared with women without cancer. In pregnancy‐related VTE risk assessment, the presence of cancer alone may be sufficient to indicate thromboprophylaxis. Tweetable abstract: Cancer in pregnancy increases the risk of VTE during pregnancy and the postpartum period. Tweetable abstract: Cancer in pregnancy increases the risk of VTE during pregnancy and the postpartum period.